2014
DOI: 10.1158/1055-9965.epi-13-0943
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Contraception before the First Birth and Endometrial Cancer Risk

Abstract: There is a well-documented reduction in endometrial cancer risk with combined oral contraceptive (COC) use. COC use before the first full-term pregnancy may affect breast cancer risk for decades, but this relationship has not been investigated in endometrial cancer. We investigated the risk for endometrial cancer with COC use before the first full-term pregnancy. Cases (n ¼ 524) from a population-based cancer registry and age-matched controls (n ¼ 1,032) were recruited between 2002 and 2006 in Alberta, Canada.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…There is a clear trend with longer use being associated with lower incidence. The incidence on an annualized basis is 0.95 for use of combined agents (Hüsing et al 2016; Cook et al 2014). Beginning OCs prior to or after the first pregnancy does not seem to have an effect (Schonfeld et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…There is a clear trend with longer use being associated with lower incidence. The incidence on an annualized basis is 0.95 for use of combined agents (Hüsing et al 2016; Cook et al 2014). Beginning OCs prior to or after the first pregnancy does not seem to have an effect (Schonfeld et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to HRT, the use of hormonal contraception is protective to the endometrium [17]. The reduction of this risk is proportional to duration of use, for every 5 years of use is associated with an RR of 0.76, and this effect persists for about 30 years, and it may be amplified as time progresses [18].…”
Section: Reasons For the Increase In The Incidence Of Ecmentioning
confidence: 99%
“…The total number of ovulatory years between menarche and menopause has been used, but this does not address the timing of COC use with respect to full-term births. Studies of breast cancer (Schlesselman, 1989; Romieu et al , 1990; Kahlenborn et al , 2006) and endometrial cancer (Cook et al , 2014) have reported a long-term effect with the use of COCs before the first full-term pregnancy (FFTP) among parous women. We therefore investigated the EOC risk associated with COC use, focusing on COC use before the FFTP.…”
mentioning
confidence: 99%